2018
DOI: 10.1021/acs.jpca.7b12152
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry and Theoretical Investigation of VNn+ (n = 8, 9, and 10) Clusters

Abstract: VN clusters were generated by laser ablation and analyzed by mass spectrometry. The results showed that VN, VN, and VN clusters were formed, and the mass peak of VN is dominant in the spectrum. The VN cluster was further investigated by a photodissociation experiment with 266 nm photons. Density functional theory calculations were conducted at the M06-2X/6-311+G(d,p) level to search for stable structures of VN ( n = 8, 9, and 10) and their neutral counterparts. The theoretical calculations revealed that the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Metal clusters have been recognized as an ideal model to probe into the mechanisms of N 2 activation and dissociation, as they are well-defined systems with specific structures and adsorption sites of atomic precision, providing insightful information relating to charge distribution, electron transfer, and changes of geometric and electronic structures in the catalytic process . Mass spectrometry, matrix-isolation infrared spectroscopy, , and infrared multiple photon dissociation (IR-MPD) have been employed to study the adsorbed N 2 on metal clusters in the gas phase. , It was found that metal clusters can adsorb multiple N 2 molecules, and a few of them such as Sc 2 , Gd 2 , Ti 2 , and Ta 2 + allow the weakening of the strong N≡N triple bond of dinitrogen and even form M 2 N 2 + products with N≡N bond dissociated. This was rationalized by a synergy effect of the σ-donation of dinitrogen toward metal and π-back-donation of the d orbitals of the transition metal to the antibonding π orbital of N 2 , resulting in significantly weakened N–N bond and subsequent dissociation under structural relaxation in sufficient internal energy. , However, it is still challenging to observe a direct reaction product with an odd number of nitrogen atoms in mild conditions, and the insights of metal cluster catalysis for N≡N bond dissociation are open to be further explored.…”
mentioning
confidence: 99%
“…Metal clusters have been recognized as an ideal model to probe into the mechanisms of N 2 activation and dissociation, as they are well-defined systems with specific structures and adsorption sites of atomic precision, providing insightful information relating to charge distribution, electron transfer, and changes of geometric and electronic structures in the catalytic process . Mass spectrometry, matrix-isolation infrared spectroscopy, , and infrared multiple photon dissociation (IR-MPD) have been employed to study the adsorbed N 2 on metal clusters in the gas phase. , It was found that metal clusters can adsorb multiple N 2 molecules, and a few of them such as Sc 2 , Gd 2 , Ti 2 , and Ta 2 + allow the weakening of the strong N≡N triple bond of dinitrogen and even form M 2 N 2 + products with N≡N bond dissociated. This was rationalized by a synergy effect of the σ-donation of dinitrogen toward metal and π-back-donation of the d orbitals of the transition metal to the antibonding π orbital of N 2 , resulting in significantly weakened N–N bond and subsequent dissociation under structural relaxation in sufficient internal energy. , However, it is still challenging to observe a direct reaction product with an odd number of nitrogen atoms in mild conditions, and the insights of metal cluster catalysis for N≡N bond dissociation are open to be further explored.…”
mentioning
confidence: 99%
“…One common way for generating clusters is to bombard of substrates with laser pulses, electrons and so on [14][15][16][17][18][19][20], which have also been employed to produce nitrogen clusters [21][22][23][24][25][26][27][28][29][30][31][32]. For example, the nitrogen discharges have been used to generate the linear centrosymmetric ground state of the N 4…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the case of a positive answer to this question, to what degree do the molecular and electronic structure parameters of such compounds, as well as their thermodynamic characteristics, depend on the nature of the M atom? There is no information in the literature about such compounds, although a number of publications were devoted to two-element chemical substances containing atoms of s -, p - or d -elements and nitrogen atoms (in particular, [ 11 , 12 ] and articles by [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] in the last 5 years). It should be noted that almost every one of these works mentioned the possible use of such compounds as potential high-energy materials.…”
Section: Introductionmentioning
confidence: 99%